'Capturing Anarchists Across Borders': The Transnational Dimensions of Italian Antimilitarist Campaigns, 1911–14. Issue 3 (2nd September 2017) - Di Paola, Pietro
Abstract: This article engages with questions of the integration of different scales of analysis in the study of labour and radical movements: 'transnational', 'national' and 'local' or 'trans-local'. The article places the study of transnational anarchism in a 'national' and 'trans-local' perspective. The analysis of the intersection between the networks of those who migrated from Italy and those who remained provides a fruitful means to uncover dynamics within the transnational anarchist movement and the interplay, in both directions, between home country, exile communities and host countries. The article focuses on the crucial, but still unexplored, contributions of communities of Italian anarchists abroad (in, among other places, London, Paris, Berne, Marseille, Barre and Buenos Aires) to the anti-militarist campaigns against the Italian colonial enterprise in Libya from 1911 to 1914, in terms of propaganda, theoretical debate, financing and countercultural production. The investigation of the initiatives of anarchist exiles and how they coordinated with their comrades in Italy provides a significant case study, not only to understand network-based transnational anarchism but also to reflect on mechanisms of political migration and their influence on the development of social conflicts.